PENERAPAN THE RECOGNITION OF STROKE IN THE EMERGENCY ROOM MENINGKATKAN KEMAMPUAN PERAWAT DALAM DETEKSI DINI STROKE: IMPLEMENTATION OF THE RECOGNITION OF STROKE IN THE EMERGENCY ROOM IMPROVES THE CAPABILITY OF NURSES IN EARLY DETECTION OF STROKE - Kristiyani Herda Rophi; Fitri Dia Muspitha (Poltekkes Kemenkes Jayapura, 2024)
Keselamatan pasien stroke sangat ditentukan dari cepat dan tepatnya penanganan awal. Tidak semua fasilitas kesehatan memiliki computed tomography scan (CT Scan) untuk penegakan diagnosis stroke. Tenaga kesehatan di puskesmas dapat menggunakan alternatif instrumen untuk screening stroke berupa sistem skoring, sehingga dapat memberikan tindakan segera untuk menurunkan kecacatan dan kematian akibat stroke. Penelitian ini bertujuan untuk mengevaluasi pengaruh penerapan the Recognition of Stroke in the Emergency Room (ROSIER) scale terhadap peningkatan kemampuan perawat dalam mendeteksi dini stroke. Penelitian ini merupakan quasi eksperiment dengan one group pre-post-test design yang dilakukan pada perawat dengan jadwal kerja di Unit Gawat Darurat (UGD) Puskesmas. Sampel penelitian berjumlah 34 perawat. Analisis data menggunakan uji Wilcoxon signed rank. Hasil penelitian menunjukkan adanya peningkatan rata-rata kemampuan deteksi dini stroke responden sebelum dan setelah penerapan ROSIER scale, dengan peningkatan sebesar 20,26 poin (8,09±5,02 dan 28,35±2,62). Pada pre-test sebanyak 34 responden (100%) berada pada kategori tingkat tidak mampu. Hasil post-test menunjukkan 32 responden (94%) pada tingkat mampu dan 2 responden (6%) pada tingkat cukup mampu. Ada pengaruh yang signifikan penerapan ROSIER scale terhadap peningkatan kemampuan perawat dalam deteksi dini stroke (p=0,000). ROSIER scale dapat dipertimbangkan penggunaannya sebagai instrumen deteksi dini stroke oleh tenaga kesehatan di setting pra-rumah sakit. The speed and accuracy of initial treatment highly determine the safety of stroke patients. Not all healthcare facilities have computed tomography scans (CT scans) to diagnose strokes. Healthcare workers at community health centers (puskesmas) can use alternative instruments for stroke screening in the form of scoring systems, allowing for immediate action to reduce disability and death due to stroke. This study aims to evaluate the impact of implementing the Recognition of Stroke in the Emergency Room (ROSIER) scale on improving nurses' ability to detect strokes early. This research is a quasi-experimental study with a one-group pre-post-test design conducted on nurses working in the Emergency Unit of a community health center (Puskesmas). The study sample consisted of 34 nurses. Data analysis was performed using the Wilcoxon signed-rank test. The results showed an increase in respondents' average early stroke detection ability before and after the implementation of the ROSIER scale, with an increase of 20.26 points (8.09±5.02 and 28.35±2.62). In the pre-test, all 34 respondents (100%) were incapable. The post-test results showed 32 respondents (94%) in the capable category and two respondents (6%) in the fairly capable category. The ROSIER scale implementation has a significant impact on improving nurses' ability to early detect strokes (p=0.000). The ROSIER scale can be considered for use as an early stroke detection instrument by healthcare workers in pre-hospital settings.